“Quantifying the global legal trade in live CITES-listed raptors and owls for commercial purposes over a 40-year period” (Avocetta, 2020)
Subsequent to the publication of the following paper in Avocetta, the authors were made aware of an error in the dataset affecting the results presented in Table 4. After re-analysing the data, the new dataset failed to uphold the original conclusions and the authors have requested a retraction of the original manuscript to sustain the integrity of their findings. Panter, C.T., Atkinson, E.D. & White, R.L. 2019. Quantifying the global legal trade in live CITES-listed raptors and owls for commercial purposes over a 40-year period. Avocetta 43(1): 23-36. Doi: https://doi.org/10.30456/ AVO.2019104